Eat pray love ([s.l.] : Columbia Pictures Industries, Inc., 2010)
Believing there's more to life than a husband, house and career, Liz Gilbert finds herself with a new appetite for life in this inspiringtrue story, based on the bestselling book. She leaves New York and embarks on a yearlong journey - travelling to Italy, India and Bali - seeking self-discovery through good food, medition and the prospect of finding true love. James Franco, Billy Crudup and Javier Bardem co-star in this sumptuous and uplifting adventure filled with humor and heart.